Analisis Pengaruh Customer Review and Rating dan promosi penjualan terhadap Minat Beli Konsumen pada platform e-commerce TikTok Shop (Studi pada Mahasiswa STIE Semarang) - Wijaya, Hamdika Dwi; Tamrin, Moh; Agatha, Fieska Diera (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This study aims to investigate the effect of online customer review and rating and sales promotion on consumer purchase intention on the Tiktok Shop e-commerce platform, with a focus on STIE Semarang students. The research population consists of STIE Semarang students who have made at least one purchase on the Tiktok Shop e-commerce platform in the last six months. A total of 100 respondents were selected as samples using the Cochran formula and the questionnaire was distributed via Google Form. Data analysis was performed using multiple linear regression. The results showed that online customer review and rating had a positive and significant effect on purchase intention on the Tiktok Shop e-commerce platform, with a calculated Fvalue of 110.591> Ftable 3.09 and a significance value of 0.001. and with a calculated tvalue of 4.599> ttable 1.660 with a significance level of 0.001. Furthermore, the calculation results show that sales promotion also has a significant influence on purchase intention, with a calculated ttvalue of 5.241 > ttable 1.660 with a significance level of 0.001. This research is expected to provide important suggestions and insights for the Tiktok Shop e-commerce platform in designing marketing strategies and effective decision making to increase consumer buying interest.